PENGARUH GAME EDUKATIF “ALFABETA ADVENTURE“ TERHADAP KEMAMPUAN MEMBACA AWAL ANAK DI TAMAN KANAK-KANAK VILLA BETA KOTA PADANG - Viola Ananta; Rismareni Pransiska (STKIP Subang, 2026)
This study was motivated by the low early reading skills of young children, particularly in recognizing letters, understanding letter sounds, and combining letters into simple syllables. The use of less interactive learning media also led to low learning motivation. This study aimed to examine the effect of the Canva-based educational game “Alfabeta Adventure” on the early reading skills of children at Villa Beta Kindergarten, Padang City. This study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The subjects were 15 children from Group B at Villa Beta Kindergarten, Padang City. Data were collected using a test consisting of 6 items. Data analysis included normality tests and hypothesis testing using a paired sample t-test with SPSS version 29.0 for Windows. The results showed a significant difference between pre-test and post-test scores of early reading skills, with a significance value of 0.001 < 0.05. The average score of children’s early reading skills increased after the intervention using the “Alfabeta Adventure” educational game. It can be concluded that the “Alfabeta Adventure” educational game is effective in improving early reading skills of young children.